PRINSIP KESOPANAN DALAM WHATSAPP MAHASISWA DENGAN DOSEN BAHASA DAN SASTRA INDONESIA - Maisun, Maisun; Kasanova, Ria (Jurnal Komposisi, 2022)
Language is a means used by humans as a means of communication, so that interactions between one and another run effectively. In interacting, humans cannot be separated from various things related to politeness which regulate how humans communicate well between speakers and their speech partners. Communication using WhatsApp is commonplace. One of them is ChatWhatsApp students to their lecturers in the form of 1) maxim of wisdom, 2) maxim of appreciation 3) maxim of agreement. Based on the analysis of the object of study in this study, it can be concluded that in ChatWhatsApp students with lecturers majoring in Indonesian language and literature, there is a lot of use of politeness maxims which are described in three, namely: maxim of wisdom, maxim of appreciation, and maxim of agreement.